Stabilization, safety, and security of distributed systems : 18th International Symposium, SSS 2016, Lyon, France, November 7-10, 2016, Proceedings /: 18th International Symposium, SSS 2016, Lyon, France, November 7-10, 2016, Proceedings. (2016) - Unknown
No abstract available